THE DEVELOPMENT OF NEXT GENERATION BLOOD PRESSURE MONITOR - ROSLI, ROSLINA (2017)
The arterial blood pressure measurement has been widely used as an essential physiological parameter in the process of preventing and detecting diseases especially in cardiovascular diseases. The conventional blood pressure measurement method based on inflation and deflation of a cuff on the upper arm provide poor wear-ability gives uncomfortable feeling to the patient for long term monitoring process. Currently, automatic and cuff-less non-invasive blood pressure monitor which can provide an accurate measurement has gained increasing attention as it can be used for daily health monitoring.